Neuropsychological consequences of volatile substance abuse: a population based study of secondary school pupils. Issue 6689 (24th June 1989) - Chadwick, O.; Anderson, R.; Bland, M.; Ramsey, J.
Abstract : OBJECTIVE–To examine the effects of volatile substance abuse on neuropsychological functioning. DESIGN–A sample of index children and matched controls were identified by a two stage procedure. Firstly, over 5000 secondary school pupils completed a screening questionnaire, and, secondly, a sample of those who acknowledged volatile substance abuse and a matched sample of those who denied the practice were assessed in detail by means of (a) individually conducted interviews and (b) toxicological examination of breath samples (to exclude those intoxicated at the time of testing). SETTING–16 Local education authority secondary schools in London. SUBJECTS–160 Pupils aged 13-16: 80 index children who had abused volatile substances to the point of intoxication at least once (confirmed by interview) and 80 controls (confirmed by interview) matched for school year, sex, and ethnic background. MEASUREMENTS AND MAIN RESULTS–Neuropsychological functioning tests provided 35 main outcome measures and were administered blind. Data on educational test performance before substance abuse began were obtained retrospectively. Information on potentially confounding social factors, such as number of siblings, tenure of housing, and parents' socioeconomic and employment state was also obtained. The index children performed significantly less well than the controls in tests of vocabulary, verbal intelligence quotient, full scale intelligence quotient, and a measure of impulsivity. When background social disadvantage was taken into account these differences were no longer significant. There were no significant associations between performance on psychological testing and frequency of abuse, and relations with other aspects of the children's history of abuse were generally weak or unsystematic. Comparisons between the results of these tests and of educational tests taken before substance abuse produced equivocal findings. CONCLUSION–Volatile substance abuse, as commonly practised by secondary school pupils, is unlikely to result in neuropsychological impairment.